Finding the Acceleration Due to Gravity Using the Hydrostatic Pressure Simulation of PhET - Ibotov, Temur; Murtazayev , Mirkamol; Allaqulov, Abdulfayz; Sagdiyeva, Sevinch; Khushnazarov, Otabek; Mamatkulova, Khadicha; Addimuminov, Akmal (Indonesian Journal of Innovation and Applied Sciences (IJIAS), 2025)
This study explored the concept of hydrostatic pressure and its relationship with various heights of water using the PhET simulation platform. This research aims to determine the value acceleration due to gravity using the hydrostatic pressure simulation of PhET. The experiment's independent variable is the water column at various heights and the dependent variable is the pressure. The method used in this study is pure experimental wherein controlled variables like atmospheric pressure were kept constant. By systematically varying the water height above the ground, the experiment examined how pressure changes respond to these variations. A straight line of best fit was formed when pressure and height were plotted, which is consistent with the theory. This result indicated that as the height of the water column increases, the pressure increases proportionally, demonstrating the direct influence of gravity and water density on hydrostatic pressure. Also, the acceleration due to gravity was measured to be 9.82 ms-2. Therefore, the following were afforded by PhET simulation in this experiment: reliable data, convenient usage, eliminating the need for sophisticated equipment, and an intuitive interface for exploring physical phenomena. This study recommends PhET for teaching and learning processes. It engages the students and provides experiential learning to teachers and students.